EFFECTIVENESS OF THINK PAIR SHARE AND SPONTANEOUS GROUP DISCUSSION TOWARDS PROBLEM SOLVING SKILL STUDENT OF X ACCOUNTING GRADERS SMK NEGERI 1 WONOSARI - Puji Rahayu; Ani Widayati (Universitas Negeri Yogyakarta, 2019)
This research is aimed to know: 1) the differences of problem solving skills in students’ learning with Think Pair Share and Spontaneous Group Discussion; 2) the effectiveness of the implementation of Think Pair Share and Spontaneous Group Discussion. This research is a quasi-experimental research involving 32 students of X AK1 and X AK3. Data collection technique was a tests. Data analysis techniques for testing the result of this research were normality test, homogeneity test, and hypothesis test with t-test. The results of this study show that: 1) There are no differences in problem solving skill between students with Think Pair Share and student with Spontaneous Group Discussion student of X Accounting graders SMK Negeri 1 Wonosari. It proved by post-test on hypothesis test with the signification in the result of independent sample t-test is greater than α = 0.05 (0,475 0,05) and t count t table (0,719 2,000). 2)There are no differences in effectiveness between students with Think Pair and student with Spontaneous Group Discussion student of X Accounting graders SMK Negeri 1 Wonosari. It proved by independent samples t-test for gain score is greater than α = 0.05 (0.786 0.05) and t count t table (0,272 2,000). Keywords: Introduction to Accounting learning, TPS, SGD, Problem Solving Skill